Developmental and Early Life Origins of Hypertension: Preventive Aspects of Melatonin - You-Lin Tain; Chien-Ning Hsu (MDPI AG, 2022)
Hypertension represents a major disease burden worldwide. Abundant evidence suggests that hypertension can originate in early life. Adverse programming processes can be prevented by early life intervention-namely, reprogramming-to avoid developing chronic diseases later in life. Melatonin is an endogenously produced hormone with a multifaceted biological function. Although melatonin supplementation has shown benefits for human health, less attention has been paid to exploring its reprogramming effects on the early life origins of hypertension. In this review, first, we discuss the physiological roles of melatonin in pregnancy, fetal development, and the regulation of blood pressure. Then, we summarize the epidemiological and experimental evidence for the early life origins of hypertension. This is followed by a description of the animal models used to examine early melatonin therapy as a reprogramming strategy to protect against the early life origins of hypertension. A deeper understanding of the developmental programming of hypertension and recent advances in early melatonin intervention might provide a path forward in reducing the global burden of hypertension.